Time to negative PCR conversion amongst high-risk patients with mild-to-moderate Omicron BA.1 and BA.2 COVID-19 treated with sotrovimab or nirmatrelvir. (April 2023) - Martin-Blondel, Guillaume; Marcelin, Anne-Geneviève; Soulié, Cathia; Kaisaridi, Sofia; Lusivika-Nzinga, Clovis; Zafilaza, Karen; Dorival, Céline; Nailler, Laura; Boston, Anaïs; Ronchetti, Anne-Marie; Melenotte, Cléa; Cabié, André; et al.
Abstract: Objectives: Our aim was to compare the clinical and virological outcomes in Omicron BA.1- and BA.2-infected patients who received sotrovimab with those in patients who received nirmatrelvir for the prevention of severe COVID-19. Methods: In this multi-centric, prospective ANRS 0003S CoCoPrev cohort study, patients at a high risk of progression of mild-to-moderate BA.1 or BA.2 COVID-19 who received sotrovimab or nirmatrelvir were included. The proportion of patients with progression to severe COVID-19, time between the start of treatment to negative PCR conversion, SARS-CoV-2 viral decay, and characterization of resistance variants were determined. A multi-variable Cox proportional hazard model was used to determine the time to negative PCR conversion and a mixed-effect model for the dynamics of viral decay. Results: Amongst 255 included patients, 199 (80%) received ≥3 vaccine doses, 195 (76%) received sotrovimab, and 60 (24%) received nirmatrelvir. On day 28, new COVID-19-related hospitalization occurred in 4 of 193 (2%; 95% CI, 1–5%) sotrovimab-treated patients and 0 of 55 nirmatrelvir-treated patients (p 0.24). One out of the 55 nirmatrelvir-treated patients died (2%; 95% CI, 0–10%). The median time to negative PCR conversion was 11.5 days (95% CI, 10.5–13) in the sotrovimab-treated patients vs. 4 days (95% CI, 4–9) in the nirmatrelvir-treated patients (p < 0.001). Viral decay was faster in the patients who received nirmatrelvir (p < 0.001). In the multi-variable analysis, nirmatrelvir and nasopharyngeal PCR cycle threshold values were independently associated with faster conversion to negative PCR (hazard ratio, 2.35; 95% CI, 1.56–3.56; p < 0.0001 and hazard ratio, 1.05; 95% CI, 1.01–1.08; p 0.01, respectively). Conclusions: Early administration of nirmatrelvir in high-risk patients compared with that of sotrovimab was associated with faster viral clearance. This may participate to decrease transmission and prevent viral resistance.